2020
DOI: 10.3390/ani10122415
|View full text |Cite
|
Sign up to set email alerts
|

Reducing versus Embracing Variation as Strategies for Reproducibility: The Microbiome of Laboratory Mice

Abstract: Irreproducibility is a well-recognized problem in biomedical animal experimentation. Phenotypic variation in animal models is one of the many challenging causes of irreproducibility. How to deal with phenotypic variation in experimental designs is a topic of debate. Both reducing and embracing variation are highlighted as strategies for reproducibility. In this theoretical review, we use variation in mouse microbiome composition as an example to analyze this ongoing discussion, drawing on both animal research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…The work presented here has empirical value in clarifying that macronutrient-matched pulse-free versus pulse-containing diets can be expected to differentially impact the gut microbiome and that pulse-type is an important variable that needs to be considered in both the design and interpretation of human studies. However, while advancing the concept of a pulse-induced ecosystem, it should be anticipated that the three components of the ecosystem will be populated by different microbial taxa in results emerging from different studies, and particularly those reported by different laboratories, in part due to factors such as a source of animals and differences among studies in animal husbandry practices [67]. Our data imply that the positive effects of pulse consumption on health may, in part, be mediated by the gut microbiota based on the magnitude of their pulse-driven community differences despite the obesogenic environment.…”
Section: Discussionmentioning
confidence: 99%
“…The work presented here has empirical value in clarifying that macronutrient-matched pulse-free versus pulse-containing diets can be expected to differentially impact the gut microbiome and that pulse-type is an important variable that needs to be considered in both the design and interpretation of human studies. However, while advancing the concept of a pulse-induced ecosystem, it should be anticipated that the three components of the ecosystem will be populated by different microbial taxa in results emerging from different studies, and particularly those reported by different laboratories, in part due to factors such as a source of animals and differences among studies in animal husbandry practices [67]. Our data imply that the positive effects of pulse consumption on health may, in part, be mediated by the gut microbiota based on the magnitude of their pulse-driven community differences despite the obesogenic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Altered intestinal bacterial loads in the mice do not account for the differences in RVwa replication, as no differences were found in bacterial numbers in the feces from groups that substantially differed in RVwa infection. It has been discussed that variations in the microbiome of experimental animals at different laboratories may affect mice phenotypes, which can be at the basis of reproducibility issues [23]. This situation would have minor effects in our case, as we showed that the sole fact of depleting the microbiota with antibiotics allowed RVwa replication.…”
Section: Discussionmentioning
confidence: 61%
“…In this context, Wuerbel et al proposed to intentionally introduce a certain level of controlled variation, to test a phenotype for its robustness against natural confounders and therefore increase the translational value for further clinical studies [219]. An excellent review published by Witjes et al discussed the pros and cons of standardization in the context of microbiome variation and concluded that standardization has to be increased when researchers conduct fundamental studies, especially those who aim at identifying disease mechanisms, to reduce study confounders, whereas more translational studies require robustness tests using mice with different microbiomes to ensure generalization and to increase the external validity of study results [220]. Possible solutions for inducing variation are either the intentional diversification of the microbiome using rather extreme measures such as the re-wilding of laboratory rodents (see Section 6.2.2) or using the microbiome as a co-factor in scientific studies (see Section 6.2.3), e.g., in multi-center studies.…”
Section: Measure To Ensure "Validity"mentioning
confidence: 99%
“…Since reproducibility is closely related to research validity, it can be seen as a measure for the generalizability and translational value of results [217], thus determining relevance of findings [218]. Re-enhancing the level of microbiological standardization increases the so-called "internal validity", which can be achieved by accounting for reciprocal host-microbiome interactions aiming at minimizing variation due to microbiological confounders [220,221]. However, the factors influencing the animal's microbiome are countless and range from housing-related factors such as food, water, caging systems, bedding material (and of course their decontaminative treatments such as autoclavation, irradiation or acidification) to host-related factors such as the animal's genetics, age and gender.…”
Section: Standardizing the Microbiomementioning
confidence: 99%